U.S. Public Health Service STD Experiments in Guatemala (1946–1948) and Their Aftermath. Issue 2 (20th March 2019) - Spector‐Bagdady, Kayte; Lombardo, Paul A.
ABSTRACT: The U.S. Public Health Service's sexually transmitted disease (STD) experiments in Guatemala are an important case study not only in human subjects research transgressions but also in the response to serious lapses in research ethics. This case study describes how individuals in the STD experiments were tested, exposed to STDs, and exploited as the source of biological specimens—all without informed consent and often with active deceit. It also explores and evaluates governmental and professional responses that followed the public revelation of these experiments, including by academic institutions, professional organizations, and the U.S. federal government, pushing us to reconsider both how we prevent such lapses in the future and how we respond when they are first revealed.